Prognostic significance of uncertain resection for metastasis in the highest mediastinal lymph node after surgery for clinical N0 non-small cell lung cancer - Marziali, Valentina; Frasca, Luca; Ambrogi, Vincenzo; Patirelis, Alexandro; Longo, Filippo; Crucitti, Pierfilippo (Frontiers in Surgery, 2023)
Background: The International Association for the Study of Lung Cancer defined types of surgical resection and considered the positivity of the highest mediastinal lymph node resected a parameter of “uncertain resection” (R-u). We investigated the metastases in the highest mediastinal lymph node, defined as the lowest numerically numbered station among those resected. We aimed to evaluate the prognostic value of R-u compared with R0. Materials and Methods: We selected 550 patients with non-small cell lung cancer at clinical Stage I, IIA, IIB (T3N0M0) or IIIA (T4N0M0) undergoing lobectomy and systematic lymphadenectomy between 2015 and 2020. The R-u group included patients with positive highest mediastinal resected lymph node. Results: In the groups of patients with mediastinal lymph node metastasis, we defined 31 R-u (45.6%, 31/68). The incidence of metastases in the highest lymph node was related to the pN2 subgroups (p<0.001) and the type of lymphadenectomy performed (p<0.001). The survival analysis compared R0 and R-u: 3-years disease-free survival was 69.0% and 20.0% respectively, and 3-year overall survival was 78.0% and 40.0% respectively. The recurrence rate was 29.7% in R0 and 71.0% in R-u (p-value<0.001), and the mortality rate was 18.9% and 51.6% respectively (p-value<0.001). R-u variable showed a tendency to be a significant prognostic factor for disease-free survival and overall survival (Hazard Ratio: 4.6 and 4.5 respectively, p-value<0.001). Conclusions: The presence of metastasis in the highest mediastinal lymph node removed seems to be an independent prognostic factor for mortality and recurrence. The finding of these metastasis represents the margin of cancer dissemination at the time of surgery, so it could imply metastasis into the N3 node or distant metastasis.